Wikileaks’ demokratiske potentiale - Mølck, Casper; Ibsen, Malte Frøslee (Politik, 2012)
WikiLeaks has faced much criticism after massive leaks of secret US military les and diplomatic cables, revealing both trivial and compromising details of the superpower’s judgments and actions in international politics. However, in this article we argue that WikiLeaks harbours a democratic potential, which so far has been overlooked, principally because the organisation’s activities have been interpreted within a traditional Weberian theory of power focused on strategic action. Relying on Martin Saar’s re ections on power, we argue that WikiLeaks is more fruitfully understood in terms of an ontological theory of power focused on the subjectivity-constituting function of power and power as a constitutive space of potential ways of being. Placing WikiLeaks within Jürgen Habermas’s diagnosis of our present social and historical context, we argue that WikiLeaks – despite its obvious faults – harbours a democratic potential by constituting the possibility for democratic criticism of globalised functional systems that increasingly undermine the necessary condi- tions for the e cacious exercise of popular sovereignty.